Antioxidant activity, phenolic profile, chlorophyll and mineral matter content of corn silk (Zea mays L): Comparison with medicinal herbs. (May 2016) - Žilić, Slađana; Janković, Marijana; Basić, Zorica; Vančetović, Jelena; Maksimović, Vuk
Abstract: Yellow, green, pinky and purple colored corn silk were harvested 5 and 25 days after emergence and compared with six medicinal herbs for total phenolics, flavonoids, anthocyanins, proanthocyanidins, chlorophylls, as well as antioxidant activity. The phenolic acid, flavonoid and mineral matter profiles of corn silks were also determined. Corn silks at the silking stage are much more suitable for use as a natural source of phenolic compounds than silks at the R4 dough stage. The content of total phenolic and flavonoid compounds in fresh silk was higher by about 2- to 4-fold than in the silk at the R4 dough stage and by about 1.2- to 2.6-fold than in the most investigated herbs. The most abundant phenolic compounds were hydroxycinnamic acid ester and luteolin derivative i.e. 3-O-caffeoylquinic acid and maysin, respectively. A high potassium content and antioxidant activity of silk are associated with its health benefit properties. Highlights: Corn silks at silking stage are suitable for use as a source of phenolic compounds. Cinnamic acids and luteolin derivatives were most abundant phenolic compounds in corn silk. Antioxidant activity of corn silks at silking stage can be compared with that of medicinal herbs. High level of potassium in corn silk is associated with its diuretic effect.